Conversations about social, emotional and mental health needs: educational psychologists’ facilitation of a collaborative joint consultation process - Underwood, Claire (2022)
With increasing rates of social, emotional and mental health (SEMH) needs in UK schools (NHS Digital, 2020) and expectations for school staff to support them (DfE, 2018), educational psychologists (EPs) are often called on for support (Sharpe et al., 2016). Although consultation is a key approach to EPs’ casework (Leadbetter, 2006), relying on interpersonal skills (Zafeiriou & Gulliford, 2020), little qualitative research focusing on the interactions within consultations exists (Newman & Clare, 2016). Furthermore, despite recognition of the impact school and home environments can have on children and young people, little research exists into joint consultations (involving home and school) within the UK.